Waste Cooking Oil Transesterification using Continuous Microwave Assisted Reactor (CMAR) - Mohd Affandi, Mohd Ali; Jolius, Gimbun; Cheng, C. K.; R. M., Yunus (Universiti Teknikal Malaysia Melaka (UTeM), 2015)
This paper presents a waste cooking oil (WCO) transesterification using a continuous microwave assisted reactor(CMAR). The free fatty acid content and fatty acid methyl estercontents in the sample were determined using gas chromatography mass spectrometry (GC-MS). The results showed an efficient conversion (up to 97.0%) of WCO to biodiesel, and the highest biodiesel yield is about 92.5%. The highest conversion of 97.4% was achieved with catalyst loading of 1.0 wt.%, methanol to oil molar ratio of 10:1, reaction temperature of 60°C and the flow rate of 308 ml/min corresponding to the reaction time of 6 minutes. The biodiesel produced in this work is within the limits of the specification described by ASTM D6751.